Hip-Hop Music As A Self-Identity Of The Planktone.Ind Community - Naufal Wildani; Sapta Sari; Sri Narti (Penerbit Jurnal Indonesia, 2023)
This study aims to find out how the process of forming self-identity in the Hip-Hop music community of Plakntone.Ind in Bengkulu City. The theory used in this study is the theory of symbolic interactionism according to George Herbert Mead (in Morissan, 2013: 225). This research uses qualitative research methods in collecting data from the field, namely through in-depth interviews, direct observation, and documentation. The results of the study stated that on the community aspect, the Planktone.Ind community founded this Hip-Hop music community to expand relations and be able to interact with the community through songs. In terms of self, the existence of the Planktone.Ind community can be accepted by society because Hip-Hop music is basically a mecca for today's music accompanied by DJ music. In the aspect of the mind, seen at the time of making the Planktone.Ind community symbol where there was debate and mutual opinion among community members. The conclusion drawn from this study is that symbolic interactionism occurs in the process of forming the self-identity of the Planktone.Ind community as a Hip-Hop music community.